A Multidimensional Chaotic Image Encryption Algorithm based on DNA Coding - Liu, Yang; Zhang, Jindong (Multimedia tools and applications, 2020)
Based on chaotic encryption technology and DNA cryptography, a multidimensional chaotic image encryption algorithm based on DNA coding is proposed in this paper. Firstly, the MD5 algorithm is used to extract the features of the image, generate a new key in association with the user key, and then encode the original image in DNA. The traditional three-dimensional Lorenz system is improved to form a four-dimensional hyperchaotic Lorenz system. According to the principle of DNA cryptography, a series of operations such as scrambling, mutation, DNA addition and DNA XOR are performed on the DNA coding sequence, and finally decoded to obtain a password image. Key space analysis, statistical analysis, known plaintext attack analysis and experimental results show that the algorithm has better image encryption performance and ability to resist various common attacks.